Creating a ‘Truer’ Language Within a Work of Fiction: The Example of Suzette Haden Elgin’s Native Tongue - Ruth MENZIES (E-REA)
Schemes for creating imaginary, ideal languages were particularly prevalent in 17th and 18th century Europe and generally arose out of a desire to simplify language and impose order so as to minimise ambiguity and thereby improve communication and understanding between peoples. Centuries later, in her feminist science-fiction novel, Native Tongue (1984), Suzette Haden Elgin embarks upon a rather different project, aimed at providing women with a language capable of expressing their specific experience of life and the world. This study aims to assess the position which Elgin’s imaginary, ideal language – Láadan – occupies between the realms of reality and fiction, truth and lies.